BUDIDAYA TERUMBU KARANG GUNA PENINGKATAN PENDAPATAN PETANI DI DESA SERANGAN DENPASAR SELATAN TAHUN 2012 - Dhyana Putra, I Gusti Agung Gede; Maba, Wayan; Nada, Made (Alam Lestari, 2012)
This study will determine how the cultivation of planting coral reefs with mediation (1) Traditional (2) Semi Modern, (3) Modern, as an effort to increase the income of farmers in Serangan village.Adult coral is an export commodity. To maintain continuity, the distinguished way of planting and harvesting coral by using a system of mediation. Traditional Mediation is a way to harvest the crop reef directly in nature, in this way of the damage to coral reefs. Modern Semi Mediation is a way of cultivating a friendly reef environment with business objectives for export, meaning that the goal is economic gain. Semi Modern Mediation cultivation is considered the best solution because it is economically profitable for farmers and maintains marine conservation. Modern Mediation is a way to cultivate coral that requires more complete equipment, which affects the high cost and also requires specialized skills.This study used a questionnaire method to accumulate data, which was then examined by comparative analysis. The results showed that cultivation can improve the quality of coral reefs by (41.8%), the selling price is more expensive by (65.5%), the economic benefits by (56.4%), more efficient operating costs by (43, 6%) and the offense is can be reduced by (76.4%). Conditions like these are positive for business and thrive in the waters of Serangan village.The result of planting reefs using Traditional Mediation shows a very small profit margin, breaks the law and causes damage to the environment. It is also difficult to sell these products as they are often rejected by the international market due to strict worldwide export regulations (CITES - Convention On International Trade In Endangered Species Of Wild Fauna And Flora) in Appendix II category, which means the extinction of species that are highly protected. The analysis Semi Modern Mediation coral farming shows that the fishermen can increase their profits. Planting coral with Modern Mediation requires special skills or expertise in the manufacture of the concrete medium used. It also requires a large investment and the equipment is expensive as well as labor intensive to move the concrete to the location in the middle of the sea. This method is considered to be less efficient for commercial purposes.It is suggested that the coral reef farmers Serangan village continue to develop and improve their methods of farming. The government needs to strictly enforce the law for those who break the rules and at the same time provide guidance and counseling for reef farmers in the area.